1981
DOI: 10.1111/j.1365-2621.1981.tb04191.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Line Heat Source Thermal Conductivity Probe

Abstract: An improved line heat source thermal conductivity probe was made to simplify the construction and extend the life of thermal conductivity probes. The accuracy of thermal conductivity measurement is also improved. The better linearity of temperature versus logarithm of time was obtained as compared to published techniques. The probe made with the heater wire and thermocouple on the outside of a sewing needle instead of inside of a hypodermic needle was checked by measuring the thermal conductivity of known samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 4 publications
1
10
0
1
Order By: Relevance
“…The higher deviations were found at higher temperatures. The obtained results were comparable with data obtained by Pan and Singh, [21] also with calculated values using equations reported Baghe-Khandan et al [32] Similar results were reported by Tsai et al [22] for restructured beef. Baghe-Khandan and Okos [23] found the same trend of increased thermal conductivity with the increase in temperature and moisture content for ground lean beef.…”
Section: Resultssupporting
confidence: 94%
“…The higher deviations were found at higher temperatures. The obtained results were comparable with data obtained by Pan and Singh, [21] also with calculated values using equations reported Baghe-Khandan et al [32] Similar results were reported by Tsai et al [22] for restructured beef. Baghe-Khandan and Okos [23] found the same trend of increased thermal conductivity with the increase in temperature and moisture content for ground lean beef.…”
Section: Resultssupporting
confidence: 94%
“…For all physical properties, each was studied using 16 replicates. Moisture content was determined following Standard Method S352.2 (ASAE 2004), using a forced-convection laboratory oven (Thelco Precision, Jovan Inc., Winchester, VA) at 103°C for 72 h. Thermal conductivity, resistivity, and diffusivity were determined with a thermal properties meter (KD2, Decagon Devices, Pullman, WA), that utilized the line heat-source probe technique (Baghe-Khandan et al 1981). Bulk density was measured by filling a standard ½-l bushel tester (Seedburo Equipment Co., Chicago, IL).…”
Section: Initial Characterization Of Dwgmentioning
confidence: 99%
“…Water activity was measured using a calibrated A w meter (Sprint TH 500, Novasina, Talstrasse, Switzerland). Thermal properties (conductivity, diffusivity, and resistivity) were determined with a meter (KD2, Decagon Devices, Pullman, WA) that utilized the line heat source probe technique (Baghe-Khandan et al 1981). Bulk density was measured using a standard bushel tester (Seedburo Equipment, Chicago, IL) as described by the USDA (1999).…”
Section: Physical Propertiesmentioning
confidence: 99%